MEYNTJES, EM Inventory of documents - MEYNTJES, EM (ARCA, 2018)
Previously attached to the Free State Archives, Bloemfontein
COVERAGE 1919 Dissertation: Suid Afrika en die Vrede van Versailles.
Keywords: MEYNTJES, EM; Inventories